Dhaka Stock Market analysis with ARIMA-LSTM Hybrid Model - Arnob, Raisul Islam; Alam, Rafatul; Alam, Alvi Ebne (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.